Urgensi Pelindungan Pekerja Rumah Tangga Sebagai Pengakuan Atas Kerja Perawatan di Indonesia - Dewi, Ni Putu Yogi Paramitha; Widiyastuti, Y. Sari Murti (Jurnal Perempuan, 2023)
Domestic workers (DWs) are in a very vulnerable position. However, the problems faced by domestic workers have not yet become a mainstream discourse, let alone transformed into public policies that provide legal protection for them. In the absence of a legal framework that can be used to claim their rights, domestic workers are one of the most vulnerable groups of workers to discrimination, violence, and exploitation. In Indonesia, advocacy for a law to protect domestic workers has been ongoing for almost two decades. However, to date, the law has not been materialised, even though the Indonesian government, when hosting the G20, advocated for the recognition of the care economy. This article aims to discuss the PPRT Bill using the 5 R’s framework (recognition, reduction, redistribution, reward, and representation) developed by the ILO. This article assesses that the PPRT Bill is generally in line with the 5R’s framework, but it still needs strengthening in several aspects, especially issues of pay, benefits, and the right to unionise.